Ultrasound Pancreatic Stimulation: A Novel Strategy for Insulin Release and Diabetes Management - Niloufar Khalafpour (Journal of Bio-X Research)
Diabetes mellitus remains a global health care challenge, promoting the search for innovative treatments. In vivo and in vitro studies have shown the potential benefits of ultrasound (US) on enhancing insulin release and reactivating pancreatic β cell function. As a novel, nonpharmacological, noninvasive, and cost-effective approach, US therapy holds promise for stimulating pancreatic function and improving insulin secretion. This review explores recent findings on US therapy, focusing on low-intensity US (LIUS) and its effects on varying treatment parameters. Despite promising results, conflicting evidence highlights the need for further investigation through large-scale clinical trials to establish the therapeutic potential of US therapy and to optimize treatment regimens for effective diabetes management. The biological response to LIUS is complex and involves multiple cell types and pathways. The mechanisms triggering these effects require further exploration. A future engineering challenge lies in designing an experimental setup to control the US-induced mechanical phenomena, enabling the evaluation of biological effects with respect to parameters such as intensity, frequency, or duty cycle.